Revelatory Landscapes. - Betsky, Aaron; Levy, Leah; MacCannell, Dean; Ross, David A. (San Francisco : San Francisco Museum of Modern Art, 2001)
The union of the disciplines of landscape design and environmental installation have created a new hybrid of art and design. Revelatory Landscapes documents four Bay Area-based, site-specific installations commissioned by the San Francisco Museum of Modern Art. With the common theme of exploring and revealing the Edge of the Urban Scene these projects - temporary and experimental in nature - suggest the boundaries and spaces created by the emotional, socioeconomic and cultural threads in the sub/urbanfabric.
biog. p. 96-99, bibliog. p. 100-102
Engels
Revelatory Landscapes, San Francisco Museum of Modern Art, San Francisco, May 15 to October 14, 2001. This exhibition is on view at the Museum and outdoor sites around the San Francisco Bay Area.
boek
Keywords: Baer, Jaimi; da Cunha, Dilip; Gustafson, Kathryn; Hargreaves Associates; Hollis, Douglas; Hood, Walter; Leader, Tom; Mathur, Anuradha; Wilson, Olly